PERANCANGAN FILM PENDEK TENTANG HAKIKAT PEREMPUAN MINANGKABAU MELALUI KABA SABAI NAN ALUIH - ETIKA FITRIA NINGSIH, Ir. Drs. Heldi, M.Si., Ph,.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of designing a short film about the nature of Minangkabau women through the Sabai Nan Aluih kaba is to provide effective information, communication about emphasis and application to Minang women in the preservation of Minangkabau cultural and cultural values. However, the issue of issues that have been found to be suboptimal interest in adolescents understanding the Sabai Nan Aluih kaba and the role of the Minangkabau women, besides that there is still not enough media to listen to views such as films in exploring traditional stories. The method used in this design is a combination of the glass box and black box methods. This method cannot be separated because these two methods have their respective portions to form a balanced element in creating a work. The analysis approach uses 5W + 1H. This creative design program goes through several stages, namely Pre-production, production, and post-production. Whereas data collection uses primary data types and secondary data. The results of the design of the main media hearings Sabai Nan Aluih film became an educational media for the community, especially Minang female adolescents, how its nature as a Minangkabau woman, can attract attention to preserve the values of tradition and culture. Besides supporting media, they are posters, flash cards, stickers, key chains, t-shirts, trailers, and Instagram accounts.Keywords: Film, Nature, Women, Minangkabau